Гео Шкурупій: homo ebriosus як суб’єкт репортажної новели - Губарєва, С. (Літературознавчі обрії. Праці молодих учених, 2010)
The paper is focused on the investigation of some specific features of such genre as short story (the novelette) by Ukrainian futurist of 20-ies of the XX century Heo Shkurupij. The writer’s innovative experiments based on the experience of «The Cursed Poets» are emphasized. The analysis is conducted in the light of symbolism, existentialism and structuralism due to comparative strategy.